2004
DOI: 10.1073/pnas.0408191101
|View full text |Cite
|
Sign up to set email alerts
|

Tumor imaging by means of proteolytic activation of cell-penetrating peptides

Abstract: We have devised and tested a new strategy for selectively delivering molecules to tumor cells. Cellular association of polyargininebased, cell-penetrating peptides (CPPs) is effectively blocked when they are fused to an inhibitory domain made up of negatively charged residues. We call these fusions activatable CPPs (ACPPs) because cleavage of the linker between the polycationic and polyanionic domains, typically by a protease, releases the CPP portion and its attached cargo to bind to and enter cells. Associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
713
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 760 publications
(732 citation statements)
references
References 41 publications
12
713
1
2
Order By: Relevance
“…A nonapeptide (HIV-Protease 1 substrate), was chosen as the target (13, Val-SerGln-Asn-Tyr-Pro-Ile-Val-Gln). [29][30][31] Nonapeptide 13 was synthesized on SU-8 prepared on Al (11a) since this had given the best results for the synthesis of Leu-Enkephalin (12) (Scheme 3). As peptide 13 was not commercially available, a synthetic standard of 14 was prepared by standard SPPS using standard PS resin with a Wang linker, 15.…”
Section: Peptide Synthesismentioning
confidence: 99%
“…A nonapeptide (HIV-Protease 1 substrate), was chosen as the target (13, Val-SerGln-Asn-Tyr-Pro-Ile-Val-Gln). [29][30][31] Nonapeptide 13 was synthesized on SU-8 prepared on Al (11a) since this had given the best results for the synthesis of Leu-Enkephalin (12) (Scheme 3). As peptide 13 was not commercially available, a synthetic standard of 14 was prepared by standard SPPS using standard PS resin with a Wang linker, 15.…”
Section: Peptide Synthesismentioning
confidence: 99%
“…Later, similar approaches were used for imaging MMP expression in the heart after myocardial infarction where an near-IR fluorescent probe was activated upon proteolytic cleavage by MMP-2 and MMP-9 (75). In another report, cellular association of polyargininebased cell-penetrating peptides is effectively blocked when they are fused to an inhibitory domain composed of negatively charged residues, which was called ''activatable cell-penetrating peptides'' (76). Cleavage of the MMPsensitive linker between the polycationic and polyanionic domains releases the cell-penetrating peptide portion and its attached cargo to bind to and enter cells.…”
Section: Imaging Mmp Expressionmentioning
confidence: 99%
“…This method provides detection of spatially localized enzymatic activity in living tissues through the accumulation of cleaved probe. ACPPs have been previously reported that target MMPs [16,17] and elastases [20] in tumors. A thrombin-activated ACPP with cleavage sequence DPRSFL, from the PAR1 receptor was recently reported for monitoring thrombin activation in atherosclerotic plaques.…”
mentioning
confidence: 99%
“…[15] Activatable cell-penetrating peptides (ACPPs) target various cargos, including fluorescent imaging agents, to sites of protease activity in vivo. [16][17][18][19] ACPPs consist of a polycationic cell-penetrating peptide attached to a cargo and a polyanionic inhibitory domain with a protease-cleavable linker. Probe activation and cargo uptake depend on localized proteolysis of the linker sequence that connects the polyanionic and polycationic domains, which converts the probe to an adherent form.…”
mentioning
confidence: 99%